Discursive Characterization of Dictamen Genre Produced by Two Institutions of the Public Administration in Chile - Meza, Paulina (2023)
The research aim is to determine the discursive characteristics variation of the Dictamen genre produced by two institutions of the Public Administration in Chile: The General Comptroller of the Republic (GCR) and the Labor Direction (LD). Within the framework of a qualitative study, we analyzed a corpus made up of 81 Dictamens (48 from the GCR and 33 from the LD), which were approached based on the characterizing criteria of the genre proposed by Parodi et al., 2009. Among the main findings, we highlight that the opinions of both institutions have the same denomination, but different purposes, a fact that allows us to establish that they correspond to different genres. Thus, the Dictamen of the GCR has as a communicative macro purpose to order something to the heads of service of public entities, while that of the LD intends to inform the labor legislation to the workers. In conclusion, the Dictamen of the CGR and the DT correspond to different genres with elements in common (circulation context, predominant and auxiliary discursive organization modes, predominant semiotic modality), but also differentiators (communicative purpose, relationship between the participants and prototypical semiotic artifact).